Methods of Solving System of Linear Equations - Baral, Aasis; Karki, Sandip; Baral, Hom Nath; Malla, Moham Bikram; Shahi, Nirak Kumar (Mid-West University Journal of Engineering & Innovation, 2025)
This paper explores the various methods used to solve systems of linear equations, a fundamental topic in mathematics with wide-ranging applications in physics chemistry, biology, engineering, and economics. The methods examined include graphical solutions, substitution, elimination, and matrix-based techniques such as Gaussian elimination and Cramer's Rule. The project aims to provide a clear understanding of each method's principles, effectiveness, and appropriate contexts for use. A comparative analysis is conducted to highlight the strengths and limitations of each approach, guiding the selection of the most suitable method for different types of problems.